2021
DOI: 10.3389/fmicb.2021.650099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Causes of Non-pathogenic Pseudomonas syringae pv. actinidiae Isolates in Kiwifruit Orchards

Abstract: Bacterial canker disease has become the largest threat to kiwifruit cultivation and production. A monomorphic subpopulation of Pseudomonas syringae pv. actinidiae biovar 3 (Psa3) is responsible for the pandemic worldwide. Diversity in pathogenicity has been found in the pandemic subpopulation and in other Psa3 subpopulations causing epidemics in China. However, the genetic bases have not yet been elucidated. In this study, 117 Psa3 isolates were identified by Psa- and Psa3-specific primers, and evaluated for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Transcriptome and qRT-PCR results showed that OmpR-like deletion led to an increase in hrpR/S transcription, while its overexpression led to a decrease in hrpR/S transcription, suggesting that OmpR-like can directly and negatively regulate hrpR/S transcription and the expression of downstream T3SS genes. Our DNA pull-down data (ProteomeXchange accession: PXD023722) [ 33 ] further supported the direct interaction between the OmpR-like protein and the promoter region of the hrpR/S gene. A recent study by Shao et al [ 40 ] also demonstrated that EnvZ-OmpR is a repressor of the T3SS in P. savastanoi pv.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Transcriptome and qRT-PCR results showed that OmpR-like deletion led to an increase in hrpR/S transcription, while its overexpression led to a decrease in hrpR/S transcription, suggesting that OmpR-like can directly and negatively regulate hrpR/S transcription and the expression of downstream T3SS genes. Our DNA pull-down data (ProteomeXchange accession: PXD023722) [ 33 ] further supported the direct interaction between the OmpR-like protein and the promoter region of the hrpR/S gene. A recent study by Shao et al [ 40 ] also demonstrated that EnvZ-OmpR is a repressor of the T3SS in P. savastanoi pv.…”
Section: Discussionmentioning
confidence: 53%
“…Previously, we performed a DNA pull-down assay using the biotin-labeled DNA sequence upstream of hrpR/S gene as a probe to detect the protein candidates potentially regulating the transcription of hrpR/S gene and found an OmpR-like transcription factor (CN228_13375, GenBank accession: AYL80818.1) as a highly reliable candidate (ProteomeXchange accession: PXD023722) [ 33 ]. In this study, the regulatory mechanism and other functions of the OmpR-like transcription factor, involved in regulating the hrpR/S gene in Psa , were explored by techniques such as gene knockout and overexpression, ChIP-seq, and RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…A similar case was found in the M227 strain isolated in China: a transposable insertion at the 930 bp upstream of HrpR caused reduced pathogenicity by attenuating the expression of TTSS and TTEs [ 17 ]. For the other three non-pathogenic strains (S2, G4, G40), the ISPsy36 transposon insertion was found at the 573 bp position of HrpR [ 30 ]. In the present work, the HrpR gene of two low-pathogenicity strains, ScPzH and ScDjyH, was interrupted at 596 bp, resulting in a mutated gene encoding a truncated protein ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Kiwifruit bacterial canker (KBC), caused by Pseudomonas syringae pv. actinidiae ( Psa ), has already become an economic threat to the kiwifruit industry worldwide ( Tahir et al, 2019 ; Li et al, 2021 ). Many efforts have been made to uncover the population structure of Psa , and at least five types of populations, including biovars 1, 2, 3, 5, and 6, have been defined based on their virulence, toxin production, and host range, of which biovar 3 is responsible for the global pandemic ( He et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%